Hipotek Kapal: Perlindungan Hukum dan Kepastian Bagi Kreditur - Pambayun, Cindy Fatika Dewi; Tan, David; Fitri, Winda (Legal Standing : Jurnal Ilmu Hukum, 2025)
Ships as collateral for mortgages in credit agreements are regulated in Articles 1162 to Article 1232 of the Civil Code and Shipping Law Number 17 of 2008. This departs from Indonesia's geographical conditions as a maritime country with important sea transportation, as well as its position in between the continents of Asia and Australia. Ships have two legal statuses, namely as movable and immovable objects. The Shipping Law states that the guarantee of a ship is determined by its region of registration, which is also linked to information about the ship and its owner in the national registration book. The nationality of the ship needs to be considered like other property rights. Banks are often hesitant to accept ship collateral due to the precautionary principle. However, the 2008 Shipping Law provides new hope for shipping entrepreneurs, even though many ships are not yet insured, making it difficult for banks to accept ships as credit collateral.